Endoscopic dacryocystorhinostomy as an option management of syndrome- related congenital dacryocystocele: a case report - Yunia Irawati; Alexander Krishna Ernanda; Florentina Priscilia; Retno Sulistyo Wardani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Congenital dacryocystocele (CD) is a rare anomaly of the medial region of the orbit, caused by distal at the level of the valve of Hasner and proximal at the level of the valve of Rosenmuller obstruction of the lacrimal system. It may present as isolated abnormalities or maybe associated with syndromes. We described a neonate with a history of bilateral enlarged lacrimal sacs below medial canthal tendon with blue-grayish color and epiphora.  Computed tomography (CT) scan resulted in congenital dacryocystocele. She was given topical antibiotics and Crigler massage as conservative treatment. In the first week, the right eye got a complete resolution. Otherwise, the left eye’s lesion was worsening. The patient underwent endoscopic dacryocystorhinostomy (En-DCR) and silicone intubation on the left eye. Epiphora resolved with no recurrence at one month follow up. Conservative treatment and En-DCR have a success rate with no complication and widely used nowadays. In the case of CD associated with a syndrome, multidiscipline workups and treatment are essential.